2021
DOI: 10.1080/07853890.2021.1943515
|View full text |Cite
|
Sign up to set email alerts
|

The role of lycopene for the amelioration of glycaemic status and peripheral antioxidant capacity among the Type II diabetes mellitus patients: a case–control study

Abstract: Lee (2021) The role of lycopene for the amelioration of glycaemic status and peripheral antioxidant capacity among the Type II diabetes mellitus patients: a case-control study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Similarly, Upritchard et al [ 4 ] supplemented T2DM patients with 500 mL of tomato juice along with Vitamin E and C for 4 weeks, and reported that lycopene supplementation did not affect plasma glucose concentration. Very recently, HbA1c and FPG levels were found to decrease significantly with the higher lycopene intake [ 105 ]. The combined application of cross-sectional, case-control, prospective cohort, and randomized placebo-controlled trials generated a discrepancy in outcomes.…”
Section: Lycopene Consumption and T2dmmentioning
confidence: 99%
“…Similarly, Upritchard et al [ 4 ] supplemented T2DM patients with 500 mL of tomato juice along with Vitamin E and C for 4 weeks, and reported that lycopene supplementation did not affect plasma glucose concentration. Very recently, HbA1c and FPG levels were found to decrease significantly with the higher lycopene intake [ 105 ]. The combined application of cross-sectional, case-control, prospective cohort, and randomized placebo-controlled trials generated a discrepancy in outcomes.…”
Section: Lycopene Consumption and T2dmmentioning
confidence: 99%
“…The effects of lycopene administration at 10 and 20 mg lycopene per kg body weight/day for 10 days was examined on the fasting blood glucose, lipids, and glycosylated haemoglobin levels, and a reversal to normality of these parameters was seen with lycopene supplementation [ 273 ]. A recent case-control study reported that lycopene intake positively correlated with peripheral antioxidant activity, antioxidant enzymes superoxide dismutase, and glutathione peroxidase levels and negatively correlated with fasting blood glucose and glycated haemoglobin (HbA1c) levels in patients with type 2 diabetes [ 274 ]. A detailed account of evidence from in vitro, animal, and human studies (cross-sectional, prospective, and two randomised controlled trials) suggesting a preventive role of lycopene and tomato-enriched diet against diabetes is provided by Zhu et al [ 80 ].…”
Section: Health Effectsmentioning
confidence: 99%
“…Lycopene has been suggested to have clinical efficacy in the treatment of diabetes. The average daily intake of dietary lycopene among diabetics was 0.04 mg/kg BW/d, and lycopene could lower oxidative stress and enhance the pathophysiology of T2DM (Leh et al 2021). Lycopene's anticancer effects on oral cancer (OC) cells reveal that it might activate the PI3K/AKT/m-TOR signaling pathway to suppress EMT and induce apoptosis in OC cells.…”
Section: Clinical Significance Of Lycopenementioning
confidence: 99%